Correlation of birth weight with other anthropometric variables in detection of low birth weight (LBW) babies (Journal of Dhaka National Medical College & Hospital, 2012)
Objective: To assess the correlation of birth weight with other anthropometric variables and their appropriateness in prediction and detection of low birth weight babies. Methodology: It was a hospital-based cross-sectional observational study, conducted over 100 newborn babies within 24 hours of their birth. Birth weight and other anthropometric variables were recorded and analyzed with statistical package for social science (SPSS-17) and Students t-test, Chi-squared (?2), ANOVA and Pearson correlation tests were done to test the hypothesis and level of significance was set as p